An investigation of factors affecting Australian small and medium enterprise performance during The Pandemic - Ali Gungor; Catherine Jill Bamforth; John Dalrymple (Journal of Innovation and Entrepreneurship)
Abstract Small and medium enterprises (SMEs) are the backbone of many countries but suffer low survival and growth rates. This research investigated the role of ambidextrous leadership (AL), entrepreneurial orientation (EO), and organisational innovation (OI) on SME firm performance (FP) (customer satisfaction and financial performance) in Australia during the Covid-19 pandemic. Data from 344 SME owners/managers was collected and analysed using structural equation modelling. The results showed partial validation between AL opening behaviour and both FP outcomes and substantial and positive influence between closing AL behaviour and both FP outcomes. Contrary to expectations, results showed a significant negative association between EO and customer satisfaction and a weak correlation between EO and financial performance. OI was identified as an antecedent for both FP outcomes confirming existing research in this area. The findings called for post-pandemic cash-strapped governments to set up a dedicated department in their Productivity Commission (or similar body) to keep abreast of emerging SME research outcomes to inform more effective and efficient SME policy. Managers are advised to undertake low level experimentation to identify optimum alignment between FP goals and environmental context, choice of innovation type and leadership approach (AL & EO) to achieve desired FP outcomes.